PKM-RSH : Uangmu Adalah Mimpimu di Masa Depan, Ayo Rencanakan Keuangan Raih Impian di SMA Negeri 2 Kota Serang - Setiawati, Achika Nurul; Puspitasari, Della; Y, Yofi; Najla, Aura Nabila At En (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Community Service (PKM) activity entitled “Uangmu Adalah Mimpimu di Masa Depan, Ayo Rencanakan Keuangan Raih Impian” was carried out by the Pamulang University Serang Campus team at SMA Negeri 2, Cipocok Jaya District, Serang City, Banten. This activity aims to improve students' financial literacy through an understanding of the importance of wise financial management as a step towards achieving dreams in the future. A qualitative approach was used to describe the effectiveness of the socialization method used. The results of the activity showed that students who previously did not understand the importance of financial literacy now have a better awareness of financial management, including distinguishing needs and wants, saving, and starting investments. The responses of active participants were conveyed through high participation in discussions and questions related to financial management strategies. This activity also succeeded in motivating students to implement a frugal and disciplined lifestyle, as well as to prepare long-term financial plans. Through this education, it is hoped that students can build positive habits in managing finances, reduce consumptive behavior, and increase their confidence in personal financial management. The positive impact achieved shows the great potential of PKM as a sustainable education program to empower the younger generation financially.